Profiling and controlling I/O‐related memory contention in COTS heterogeneous platforms. (10th November 2021) - Zini, Matteo; Cicero, Giorgiomaria; Casini, Daniel; Biondi, Alessandro
Abstract: Motivated by the increasing number of embedded applications that make use of traffic‐intensive I/O devices, this work studies the memory contention generated by I/O devices and investigates on the regulation of the bus traffic they generate by means of COTS regulators, namely the QoS‐400 by Arm. To this purpose, the behavior of the QoS‐400 regulators is analytically characterized and then, taking the Xilinx Ultrascale+ as a reference modern heterogeneous platform, a software infrastructure to control such regulators from Linux is proposed. As an experience report, this article presents the results of an extensive experimental evaluation, based on both benchmarks and microbenchmarks, aimed at validating the effectiveness of QoS‐400 regulators in predictably controlling I/O‐related memory traffic, as well as assessing the impact of the regulation on software applications and I/O devices themselves.